Review of Islamic Law on The Mangdati Event in The Traditional Wedding of Toba Batak - Irvan Doly Syahputra Siregar; Muhammad Mahmud Nasution (Journal Equity of Law and Governance, 2024)
The main problem in this research is related to the existence of customs or traditions in Batak Toba traditional marriages which have been implemented for a long time and have been passed down from generation to generation, but there is no review of Islamic law regarding this custom. This research aims to examine the implementation of Mangadati and will be reviewed through Islamic law. This type of research is empirical using qualitative methods. From this research it can be seen that the Toba Batak people still carry out Mangadati in marriage, There are three research results in this article, namely: [1] Mangadati is a custom that is carried out at weddings to pay customary debt based on Dalihan Na Tolu, [2] According to Batak Toba Mangadati custom, it is something that must be carried out, and has sanctions, [3] Mangadati reviewing Islamic law is valid and permissible and It is not mandatory to carry it out because according to Islamic law, marriages that are in line with community customs are permissible and legal to carry out as long as they do not conflict with the Shari'ah, smell of immorality, and are from unlawful assets.